Determining Factors of Financial Performance and Firm Value: A Case Study of a Rice Company in Chengdu, China - Huang, Hua (Scholar: Human Sciences, 2025)
Purpose: This study explores the factors affecting the financial performance and firm Value of a rice company in Chengdu City, China. The research framework reveals the causal relationships among corporate social responsibility, risk management, corporate governance, firm Size, financial performance, and firm value. Research Design, Data, and Methods: This study employs a quantitative research method, conducting a questionnaire survey on 500 employees of a selected company in Chengdu City, China. Non-probability sampling techniques are judgmental, and quota sampling. To analyze the data, we used confirmatory factor analysis and structural equation modeling to examine the model’s fit, reliability, and construct validity. Results: The research results indicate that corporate social responsibility, risk management, and corporate governance do not have a significant impact on financial performance, while corporate governance has a significant influence on firm value. In addition, firm size positively impacts financial performance and significantly affects firm value through financial performance as a mediating variable. Corporate governance has the most significant impact on the company, followed by firm Size and financial performance. Conclusion: It is suggested that corporate governance be strengthened further and strategies for firm size expansion be explored to help a company formulate more accurate and effective business strategies, thereby improving financial performance and firm value.